Hormone spiral in treatment of progesterone‐induced stomatitis - Frank‐Jakob Sandbakk; Sigbjørn Løes; Torbjørn Ø. Pedersen (Clinical Case Reports, 2020)
Abstract Hormonal changes in the menstrual cycle may cause autoimmune progesterone‐induced stomatitis. This case illustrates that insertion of a hormone spiral can be a treatment option to reduce mucosal lesions and symptoms.